1983
DOI: 10.1016/s0001-2092(07)69557-x
|View full text |Cite
|
Sign up to set email alerts
|

Movement of personnel and wound contamination

Abstract: We studied the association between the movement of operating room personnel and bacterial contamination of the operative field during 12 clean operations. Settle plates placed on the patient's chest and instrument table were exposed during the operation. As a control, settle plates were exposed in the same locations when no personnel and patients were in the room. Bacterial contamination of the aseptic field was categorized as disseminating (Group A: greater than 42 combined movements) and nondisseminating (Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
0
10
0
2
Order By: Relevance
“…For example, the use of the OR door as a measure of movement of personnel has been chosen as an index of correct procedure based on the finding that the reduction of movement reduces bacterial counts in the air 18,19 and wound contamination. 20 Regarding the individual indices of correct procedure, the data on walking in and out of the OR deserves further comment. Since walking in and out of the OR is sometimes necessary, any attempt to reduce the use of the door ought to take into account the reasons for using the door.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the use of the OR door as a measure of movement of personnel has been chosen as an index of correct procedure based on the finding that the reduction of movement reduces bacterial counts in the air 18,19 and wound contamination. 20 Regarding the individual indices of correct procedure, the data on walking in and out of the OR deserves further comment. Since walking in and out of the OR is sometimes necessary, any attempt to reduce the use of the door ought to take into account the reasons for using the door.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a direct correlation between the activity level of OR personnel and bacterial counts in the OR air was shown [97, 98]. Therefore, minimizing the number of personnel in the OR, using a sub-sterile hallway for entry, storing the implants in the room are likely to help improve the air quality in the OR environment.…”
Section: The Operation Daymentioning
confidence: 99%
“…They concluded that people are the major source of environmental contamination in the operating room and unnecessary personnel should be minimized. Quraishi further confi rmed that increased activity with OR personnel led to a higher rate of surgical fi eld contamination during clean procedures (Quraishi et al 1983 ). Not surprisingly, circulating nurses and implant techni-cians/sales representatives have been implicated to be the major source of traffi c (Panahi et al 2012 ).…”
Section: Operating Room Traffi C and Intraoperative Radiologymentioning
confidence: 98%